Innovative Approaches to the Formation and Development of the Startup Ecosystem - DEMIANENKO, Nataliia; YASNOLOB, Ilona; GORB, Oleg; Zoria, Oleksii; CHIP, Liudmyla; PESTSOVA-SVITALKA, Oksana; DUBOVYCH, Olesia; SHVEDENKO, Pavel; BARDINA, Tetiana (Journal of Environmental Management and Tourism, 2021)
The article is devoted to considering the peculiarities of startup ecosystem formation. Modern theoretical views on the definition of startup ecosystem have been studied. The author’s definition of “startup ecosystem” term has been given. Innovation and entrepreneurial ecosystems aimed at creating innovative products and services by startup companies have been analyzed. The structural elements of startup ecosystem under endogenous and exogenous changes in the business environment have been singled out. The situation of startup development in Ukraine and their further prospects have been analyzed. Emphasis has been placed on the formation of entrepreneurial universities as an important component of the ecosystem. The experience of leading countries in the implementation and formation of startup ecosystem has been studied and adapted.